Security, equality, and the clash of ideas: Sweden's evolving anti-trafficking policy - Bucken-Knapp, Gregg (Human rights review, 2012)
Seeking to explain the emergence of anti-trafficking initiatives, scholars have explored two sets of ideas—national security and gender equality—thought to shape policy. In this study, we examine whether such ideational influence accounts for Sweden's evolving anti-trafficking policy over the past decade. As powerful domestic ideas about gender inequality informed the adoption of an abolitionist prostitution policy in the 1990s, one would expect similar ideas to influence domestic responses to the related issue of cross-border trafficking. However, our case study shows that the policy area of trafficking has largely followed a different ideational path. Gendered ideas, periodically nested in a human rights discourse, have been salient in the public debate on trafficking in human beings, especially during the campaign to boycott the 2006 FIFA World Cup. However, they have exerted substantially less influence on Swedish legislative initiatives to combat trafficking, with security concerns still holding sway.